Birth weight, childhood and adolescent growth and diabetes risk factors in 21-year-old Asian Indians: the Pune Children's Study. (5th June 2021) - Kumaran, Kalyanaraman; Lubree, Himangi; Bhat, Dattatray S.; Joshi, Suyog; Joglekar, Charudatta; Yajnik, Pallavi; Bhave, Sheila; Pandit, Anand; Fall, Caroline H.D.; Yajnik, Chittaranjan S
Abstract: Our objective was to investigate associations of body size (birth weight and body mass index (BMI)) and growth in height, body fat (adiposity) and lean mass during childhood and adolescence, with risk markers for diabetes in young South Asian adults. We studied 357 men and women aged 21 years from the Pune Children's Study birth cohort. Exposures were 1) birth weight, 21-year BMI, both of these mutually adjusted, and their interaction, and 2) uncorrelated conditional measures of growth in height and proxies for gain in adiposity and lean mass from birth to 8 years (childhood) and 8 to 21 years (adolescence) constructed from birth weight, and weight, height, and skinfolds at 8 and 21 years. Outcomes were plasma glucose and insulin concentrations during an oral glucose tolerance test and derived indices of insulin resistance and secretion. Higher 21-year BMI was associated with higher glucose and insulin concentrations and insulin resistance, and lower disposition index. After adjusting for 21-year BMI, higher birth weight was associated with lower 120-min glucose and insulin resistance, and higher disposition index. In the growth analysis, greater adiposity gain during childhood and adolescence was associated with higher glucose, insulin and insulin resistance, and lower disposition index, with stronger effects from adolescent gain. Greater childhood lean gain and adolescent height gain were associated with lower 120-min glucose and insulin. Consistent with other studies, lower birth weight and higher childhood weight gain increases diabetes risk. Disaggregation of weight gain showed that greater child/adolescent adiposity gain and lower lean and height gain may increase risk.